Our Penetrating Keratoplasty Results - Yılmaz, Turgut; Kükner, Şahap; Aydemir, Orhan; Çelebi, Serdal; Ulaş, Fatih (Fırat University, 2002)
Aim: Penetrating keratoplasty was evaluated between July 1993 and July 2000 in our clinic. Material and Methods: 102 penetrating keratoplasty operations have been performed on 86 patients. The follow up periods of our cases were between five months and thirty-two months, the average follow up period was six-teen months. Results: The graft was clear in 90 (88.2%) eyes of 102 cases which were followed up between July 1993 and July 2000. Visual rehabilitation was obtained in 81 (79.4%) cases. Conclusion: Penetrating keratoplasty is a successful surgical technique with excellent long term results and relatively low complication rate.

Amaç: Kliniğimizde Haziran 1993 – Haziran 2000 tarihleri arasında yapılan penetran keratoplasti ameliyatları değerlendirildi. Gereç ve Yöntem: Farklı tanılar ile 86 hastanın 102 gözüne penetran keratoplasti uygulanmıştır. Olgularımız en kısa 5 ay, en uzun 32 ay olmak üzere ortalama 16 ay takip edilmiştir. Bulgular: Haziran 1993 – Haziran 2000 tarihleri arasında takip edilen 102 olgunun 90' ında (%88.2) grefon şeffaf olarak bulunmuştur. 81 olguda (%79.4) görme keskinliğinde artma sağlanmıştır. Sonuç : Penetran keratoplasti, başarı oranı yüksek, iyi prognozlu ve komplikasyon oranları kabul edilebilir nitelikte bir cerrahi yöntemdir.
PENETRAN KERATOPLASTİ SONUÇLARIMIZ